Working Fluid Candidates Selection for 100kW Ocean Thermal Power Generation Based on Environmental, Safety, and Thermodynamic Constrains - Burhanuddin Halimi; R Y Atolah; E Julianti; I M W Kastawan (TELKA - Jurnal Telekomunikasi, Elektronika, Komputasi dan Kontrol, 2020)
Due to its equatorial location, Indonesia has a huge amount of ocean thermal energy resource. However, this alternative renewable energy resource is still not well developed yet. In this paper, a selection procedure of working fluid for a 100 kW ocean thermal power generation is presented. The screening process was based on environmental, safety and thermodynamic constrains to obtain the best working fluid for this application. Five working fluid candidates are analyzed i.e. ammonia, butane, butene, isobutane, and isobutene. In term of environmental and safety aspects, ammonia is the best solution. But in thermodynamic point of view, isobutane shows the highest power conversion efficiency of 6.13%, whereas ammonia’s efficiency is only 1.87% for the same power output.